Crime, prosecutors, and the certainty of conviction - Horst Entorf (Institute for the Study of Labor (IZA), 2011)
This paper tests predictions of a structural, augmented supply-of-offenders model regarding the relative effects of police, public prosecution and courts, respectively, on crime. Using detailed data on the different stages of the criminal prosecution process in Germany, empirical evidence suggests that public prosecutors and their influence on the probability of conviction play a major role in explaining the variation of crime rates, while the impact of the severity of punishment is small and insignificant.
urn:nbn:de:101:1-201105173059
Keywords: K14; K41; C23; 330; general deterrence; certainty of punishment; public prosecutors; informal punishment; panel data; Kriminalpolitik; Strafverfahren; Wirkungsanalyse; Kriminalität; Schätzung; Deutschland